Revisión narrativa: células madre mesenquimales de cordón umbilical y osteoartritis (2026)
Osteoarthritis (OA) is the leading cause of articular pain in adult patients, with a high worldwide prevalence and a trend towards increasing. By 2050, 642 million people are expected to suffer from knee OA. Current treatment focuses on measures to prevent progressive joint wear and control symptoms such as pain. Research in regenerative medicine, including the infiltration of platelet-rich plasma, has not yet provided solid evidence for its efficacy. With the advent of cellular therapy, the isolation and expansion of mesenchymal stem cells (MSCs) from various origins have shown promise in reducing inflammation and creating a suitable environment for the regeneration of articular cartilage. This narrative review focuses on umbilical cord-derived mesenchymal stem cells (UC-MSCs), which have certain advantages over other types of MSCs. It summarizes the various clinical trials conducted in recent years, based on a search of multiple databases.